Image completion based on statistical texture analysis - Zarif, S. (SPIE, 2015)
Image completion is an active subject in image and video processing, which deals with the recovery of original data. Most previous image completion techniques required extensive searches to find the most suited texture to repair the damaged area. In addition, visual artifacts tend to appear when the damaged area is large. We present a fast texture synthesis and image completion method that does not require an extensive search process. The proposed method is based on gray-level co-occurrence matrix and weighted two-side hole filling. The method gives high quality results compared with state-of-the-art methods. It reduces the time from hundreds of seconds to a few milliseconds and is able to repair large damaged areas without artifacts or shadows. Â© 2015 SPIE and IS&T.